A randomised controlled trial to investigate the efficacy of an oxalate strip for the management of dentine hypersensitivity pain. (July 2019) - Bahal, Priya; He, Tao; Zou, Yuanshu; Davies, Maria; Chapman, Nick; Seong, Joon; West, Nicola
Abstract: Objectives: To compare a 3.14% potassium oxalate strip and 8% arginine calcium carbonate toothpaste for the reduction of dentine hypersensitivity after 2 and 4 weeks. Methods: This was an examiner-blind, parallel study in 80 healthy adults with dentine hypersensitivity (Schiff score >2) in >1 tooth. After acclimatisation, participants were randomised to the oxalate desensitising strip with fluoride toothpaste or the arginine desensitising toothpaste control which also contained fluoride. Products were applied under supervision of study staff after measuring baseline sensitivity, thereafter the strip or control toothpaste (fingertip application) was applied after 1 and 2 weeks, and teeth brushed twice-daily with the fluoride (test group) or the fluoridated arginine control toothpaste. Sensitivity was assessed following airblast (Schiff and VAS) and tactile stimuli (Yeaple probe) at baseline, 2 and 4 weeks. Results: Both groups showed significant reductions from baseline in VAS, Schiff and Yeaple sensitivity scores after 2 and 4 weeks (p < 0.0005). The oxalate group had significantly lower Schiff and higher Yeaple probe scores compared to control after both time points (p < 0.0002 and p < 0.05), but while scores favoured the oxalate group, there were no significant differences in VAS. Conclusions: This study demonstrated application of a 3.14% potassium oxalate strip combined with toothbrushing with paste was more effective in pain management of dentine hypersensitivity than brushing with arginine toothpaste. Clinical Significance: Treatment of sensitive teeth with the oxalate strip reduced dentine hypersensitivity after 2 and 4 weeks to a significantly greater degree than a positive control sensitivity toothpaste demonstrating that oxalate strips are an effective targeted treatment for dentine hypersensitivity sufferers.